Efectos del cambio climático, en la incidencia de plagas en los cultivos - Ronquillo Montes, Adrián Eduardo (2022)
Thanks to the impact generated by human beings, the concentration of greenhouse gases in the atmosphere has increased drastically, causing high proportions of damage to agriculture and natural ecosystems. This research addressed the issue related to the effects of climate change on the incidence of pests in agricultural crops, due to the fact that variations in the climate are manifesting themselves, causing severe damage to agricultural fields and with it, a greater attack of aggressive pests on the main crops of economic and food importance, generating significant economic losses to farmers. The purpose of the research was to determine the relationship between climate change and agricultural pests. In addition, to know how climatic variations influence the frequent attack of pests on crops. The methodology used was the compilation of information from bibliographic sources such as scientific journals, theses, web pages and books. This information was analyzed and summarized in a timely manner. According to the analysis carried out, it was concluded that climate change has an enormous influence on agricultural pests, since their vital processes are interrelated with the variations that occur in the climate; therefore, any change in climatic factors will have a great impact on the intensity of pest attacks on crops. Among the factors that most favor the growth, development and reproduction of agricultural pests, it is established that temperature is the main factor responsible for accelerating the life cycle of pests.